Development of CD4 T Cell Dependent Immunity Against N. brasiliensis Infection - Harvie, Marina; Camberis, Mali; Le Gros, Graham (Frontiers in Immunology, 2013)
Of all the microbial infections relevant to mammals the relationship between parasitic worms and what constitutes and regulates a host protective immune response is perhaps the most complex and evolved. Nippostrongylus brasiliensis is a tissue migrating parasitic roundworm of rodents that exemplifies many of the salient features of parasitic worm infection, including parasite development through sequential larval stages as it migrates through specific tissue sites. Immune competent hosts respond to infection by N. brasiliensis with a rapid and selective development of a profound Th2 immune response that appears able to confer life long protective immunity against reinfection. This review details how the lung can be the site of migrating nematode immune killing and the gut a site of rapid immune mediated clearance of worms. Furthermore it appears that N. brasiliensis induced responses in the lung are sufficient for conferring immunity in lung and gut while infection of the gut only confers immunity in the gut. This review also covers the role of IL-4, STAT6 and the innate cytokines IL-25, IL-33 and TSLP in the generation of CD4-mediated immunity against N. brasiliensis reinfection and discusses what cytokines might be involved in mediated killing or expulsion of helminth parasites.